Proceso de atención nutricional en paciente masculino de 42 años con cirrosis hepática. - Zambrano Toaza, Evelyn Mariela (2023)
Liver cirrhosis is the result of chronic liver disease characterized by liver fibrosis and regenerative nodules with fluctuations in protein and lipid metabolism. For this reason, the increase in nutritional needs forces the human body to supply the needs, which leads to the deterioration of nutritional status. Pathology has a high mortality rate worldwide, especially among Men due to chronic consumption of alcohol and other diseases. The present case analysis is based on a 42-year-old male patient with liver cirrhosis, Currently the therapeutic purpose of the pathology is to improve the nutritional status of the patient, correctly provide the necessary nutrients and reduce basic complications. The patient was evaluated by anthropometric, biochemical, clinical and dietary methods and showed correct muscle structure and minimizing the underlying complications. Therefore, it is essential to provide a comprehensive procedure based on adequate calorie and protein intake